Profile of paediatric rheumatology specialists and services in the state of São Paulo - Terreri, Maria Teresa; Campos, Lucia Maria Arruda; Okuda, Eunice Mitiko; Silva, Clovis Artur Almeida; Sacchetti, Silvana Brasilia; Marini, Roberto; Ferriani, Virginia Paes Leme; Ventura, Maria Heloiza; Fernandes, Taciana; Sato, Juliana de Oliveira [UNESP]; Fernandes, Elizabeth C.; Len, Claudio; et al. (Elsevier Editora Ltda, 2013)
Introduction: Paediatric rheumatology (PR) is an emerging specialty, practised by a limited number of specialists. Currently, there is neither a record of the profi le of rheumatology patients being treated in Brazil nor data on the training of qualifi ed rheumatology professionals in the country. Objective: To investigate the profi le of PR specialists and services, as well as the characteristics of paediatric patients with rheumatic diseases, for estimating the current state of rheumatology in the state of São Paulo. Patients and methods: In 2010, the scientifi c department of PR of the Paediatric Society of São Paulo administered a questionnaire that was answered by 24/31 accredited specialists in PR practising in state of São Paulo and by 8/21 institutions that provide PR care. Results: Most (91%) of the surveyed professionals practise in public institutions. Private clinics (28.6%) and public institutions (37.5%) reported not having access to nailfold capillaroscopy, and 50% of the private clinics reported not having access to acupuncture. The average duration of professional practise in PR was 9.4 years, and 67% of the physicians had attended postgraduate programmes. Seven (87.5%) public institutions perform teaching activities, in which new paediatric rheumatologists are trained, and fi ve (62.5%) offer postgraduate programmes. Two-thirds of the surveyed specialists use immunosuppressants and biological agents classifi ed as “restricted use” by the Health Secretariat. The disease most frequently reported was juvenile idiopathic arthritis (29.1-34.5%), followed by juvenile systemic lupus erythematosus (JSLE) (11.6-12.3%) and rheumatic fever (9.1-15.9%). The incidence of vasculitis (including Henoch-Schönlein purpura, Wegener’s granulomatosis, and Takayasu’s arteritis) and autoinfl ammatory syndromes was higher in public institutions compared to other institutions (P = 0.03, P = 0.04, P = 0.002, and P < 0.0001, respectively). Patients with JSLE had the highest mortality rate (68% of deaths), mainly due to infection. Conclusion: The fi eld of PR in the state of São Paulo has a signifi cant number of specialists with postgraduate degrees who mostly practise at teaching institutions with infrastructures appropriate for the care of high-complexity patients.

Introdução: A reumatologia pediátrica (RP) é uma especialidade emergente, com número restrito de especialistas, e ainda não conta com uma casuística brasileira sobre o perfi l dos pacientes atendidos e as informações sobre a formação de profi ssionais capacitados. Objetivo: Estudar o perfi l dos especialistas e dos serviços em RP e as características dos pacientes com doenças reumáticas nessa faixa etária a fi m de estimar a situação atual no estado de São Paulo (ESP). Pacientes e métodos: No ano de 2010 o departamento científi co de RP da Sociedade de Pediatria de São Paulo encaminhou um questionário respondido por 24/31 especialistas com título de especialização em RP que atuam no ESP e por 8/12 instituições com atendimento nesta especialidade. Resultados: A maioria (91%) dos profi ssionais exerce suas atividades em instituições públicas. Clínicas privadas (28,6%) e instituições (37,5%) relataram não ter acesso ao exame de capilaroscopia e 50% das clínicas privadas não tem acesso à acupuntura. A média de tempo de prática profi ssional na especialidade foi de 9,4 anos, sendo 67% deles pós-graduados. Sete (87,5%) instituições públicas atuam na área de ensino, formando novos reumatologistas pediátricos. Cinco (62,5%) delas têm pós-graduação. Dois terços dos especialistas utilizam imunossupressores e agentes biológicos de uso restrito pela Secretaria da Saúde. A doença mais atendida foi artrite idiopática juvenil (29,1%-34,5%), seguida de lúpus eritematoso sistêmico juvenil (LESJ) (11,6%-12,3%) e febre reumática (9,1%-15,9%). Vasculites (púrpura de Henoch Schönlein, Wegener, Takayasu) e síndromes autoinfl amatórias foram mais incidentes nas instituições públicas (P = 0,03; P = 0,04; P = 0,002 e P < 0,0001, respectivamente). O LESJ foi a doença com maior mortalidade (68% dos óbitos), principalmente por infecção. Conclusão: A RP no ESP conta com um número expressivo de especialistas pós-graduados, que atuam especialmente em instituições de ensino, com infraestrutura adequada ao atendimento de pacientes de alta complexidade.
Profile of paediatric rheumatology specialists and services in the state of São Paulo
Keywords: Paediatric rheumatology; Epidemiology; Registry; Reumatologia pediátrica; Epidemiologia; Registro